POTENCIAIS BIOLÓGICOS E COMPOSIÇÃO QUÍMICA DAS FOLHAS DE Tarenaya aculeata - SILVA, Larissa Pinto de Oliveira; DUARTE, Bianca Ferreira; LIMA-JUNIOR, Sidnei Eduardo; NOGUEIRA, Claudio Rodrigo; CARDOSO, Claudia Andrea Lima (ANAIS DO ENIC, 2026)
.